Beginning PHP5, Apache, and MySQL Web development - Naramore, Elizabeth (Wiley Pub., 2005)
"Featuring new information on the features and functions of the latest upgrades - MySQL 4.0.X, PHP5, and Apache 2.0 - this book boasts a working Web site application and numerous updates throughout the text. The multi-platform approach addresses installation and usage on both Linux and Windows, and two common-themed, reusable Web sites are examined. Upon completion of this book, you'll be able to create well designed, dynamic Web sites using open source tools." "This book is for beginners who are new to PHP and who need to learn quickly how to create Web sites using open source tools. Some basic HTML knowledge is helpful but not essential."--Jacket